Network Comparison of Inflammation in Colorectal Cancer and Alzheimer's Disease. (26th July 2015) - Park, Sungjin; Yu, Seok Jong; Cho, Yongseong; Balch, Curt; Lee, Jinhyuk; Kim, Yon Hui; Nam, Seungyoon
Abstract : Recently, a large clinical study revealed an inverse correlation of individual risk of cancer versus Alzheimer's disease (AD). However, no explanation exists for this anticorrelation at the molecular level; however, inflammation is crucial to the pathogenesis of both diseases, necessitating a need to understand differing signaling usage during inflammatory responses distinct to both diseases. Using a subpathway analysis approach, we identified numerous well-known and previously unknown pathways enriched in datasets from both diseases. Here, we present the quantitative importance of the inflammatory response in the two disease pathologies and summarize signal transduction pathways common to both diseases that are affected by inflammation.